Diagnosing Obstacles to Speed and Reliability with High-Resolution Automatic Vehicle Locator Data: Bus Time Budgets. Issue 12 (December 2021) - Lind, Eric; Reid, Joseph
Transit riders consistently rate speed and reliability of service as primary drivers of satisfaction, and transit agencies can help retain and grow ridership by improving these components of service. The challenge for transit agency staff is to identify when and where they should focus efforts to improve service quality. Here we propose an approach to data analysis that identifies and isolates specific aspects of service that are limiting speed and reliability. In-vehicle travel time can be decomposed into time spent in motion and time stopped. Time in motion is often dependent on factors common to general traffic, whereas time stopped has some features in common with general traffic (i.e., traffic signals) and some unique to buses (i.e., passenger dwell). Other sources of delay from serving a bus stop include deceleration, acceleration, and signal delay. To improve overall travel time, transit agencies must prioritize interventions that will contribute the most to improving speed and reliability. We used high-resolution automatic vehicle locator data to assign components of speed and reliability within a trip-level "time budget." We compared typical time budget components across service types, and used the time budget approach to evaluate local service and Rapid bus service operating simultaneously on the same alignment. Results of the delay and variability quantifications suggested particular interventions, as well as the expected size of the resulting effect. With limited resources, the bus time budget approach could aid understanding and prioritization of transit agency efforts to improve speed and reliability.